FIRST : A Market-Based Approach to Evaluate Financial System Risk and Stability - Avesani, Renzo (Washington, D.C. : International Monetary Fund, 2005)
This paper presents background work that has been the basis for the development of the market and credit risk indicators (MRI and CRI, respectively) as published in the IMF's Global Financial Stability Report (GFSR) since September 2004. The fundamental idea was to build a set of Financial Indicators on Risk and Stability (FIRST) that could reflect the market perceptions for current and future stress on financial institutions. The focus of the analysis is mainly on large, complex financial institutions (LCFIs) operating in the most advanced financial markets, MRI and CRI have also been applied to internationally active commercial banks and insurance companies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet